2013
DOI: 10.1111/rge.12002
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical and Microbiological Analysis of Sambe Hot Springs, Shimane Prefecture, Japan

Abstract: Microbiological contribution to the formation of the manganese deposits in Sambe hot springs, Shimane, was investigated in combination with water chemistry, characterization of sediments and microbial community structure. Analysis of bacterial and fungal community structure based on DNA extracted from a Mn-oxidizing enrichment culture indicated close matches with Pseudomonas putida, Phoma sp. and Plectosphaerella cucumerina, all Mn-oxidizing microorganisms. These sediments were poorly crystalline and formed at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…This fungal species is known as Mn-oxidizing and, together with the dominant bacteria Pseudomonas spp. identified from water samples, was previously isolated from Mn oxide deposits of the Sambe hot springs in Japan [67,68]. Mn sediments in natural environments are closely related to microbial Mn-oxidizing activity [69].…”
Section: Discussionmentioning
confidence: 99%
“…This fungal species is known as Mn-oxidizing and, together with the dominant bacteria Pseudomonas spp. identified from water samples, was previously isolated from Mn oxide deposits of the Sambe hot springs in Japan [67,68]. Mn sediments in natural environments are closely related to microbial Mn-oxidizing activity [69].…”
Section: Discussionmentioning
confidence: 99%
“…as the only Mn(II)-oxidizing bacterial species. 20) In the present study, enrichment on selective solid media revealed only single type of black colored bacterial colonies, which turned out to be Pseudomonas sp. The results ).…”
Section: Resultsmentioning
confidence: 95%
“…The 16S rRNA gene sequence (135 bp) of Pseudomonas sp. previously detected from the site by DGGE 20) was not identical (94% homologous) to that of strain MM1, indicating that there is some phylogenetic diversity within the genus at the site. Consensus phylogenetic tree based on the 16S rRNA gene sequence shows the position of strain MM1 within the Pseudomonas branch and its relationship with other members of Mn(II) oxidizers (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations